Two new species of Afronurus Lestage, 1924, from Hong Kong, China (Ephemeroptera: Heptageniidae) - Braasch, Dietrich; Jacobus, Luke M. (Zootaxa, 2011)
Afronurus alces, sp. nov., and A. otus, sp. nov., are described based on male adult material from Hong Kong, China. Afronurus alces, sp. nov., has penes that are extraordinarily differentiated and laterally expanded. Afronurus otus, sp. nov., has a distinctive bifurcation at the tip of each penis lobe, with sharply pointed prongs that are subequal in size. Discussion is provided about the state of systematics for the tribe Afronurini Webb & McCafferty, 2007, with special reference to the genus Afronurus Lestage, 1924.